THE APPLICATION OF RESTORATIVE JUSTICE IN RESOLVING MINOR ASSAULT CRIMES WITHIN THE JURISDICTION OF THE SUKOHARJO POLICE - Hernanda Fatchurrohman; Ariy Khaerudin; Yulian Dwi Nurwanti (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The application of restorative justice in resolving minor assault offenses is a law enforcement effort that prioritizes peace, accountability, and the restoration of social relations in the community. This study aims to analyze the implementation of restorative justice in resolving minor assault offenses within the jurisdiction of the Sukoharjo Police and to examine the effectiveness of its practice. The research applies an empirical legal method with a sociological-juridical approach through statutory review, literature study, police statistical data, and field-oriented analysis. The findings show that restorative justice at the Sukoharjo Police has been implemented relatively effectively, as reflected in the tendency toward case settlement through peace mechanisms and the reduction of prolonged conflict between victims and offenders. Restorative settlement provides faster legal certainty, supports direct recovery for victims, and creates more harmonious relations between the parties. Nevertheless, implementation still faces several obstacles, including limited public understanding of restorative justice and the need to strengthen mediation skills among police officers. Therefore, broader public outreach, improved professionalism of investigators, and stronger supervision over peace agreements are required to ensure that restorative justice is carried out transparently, objectively, and fairly.